Expenditures and revenues: testing for causality in Sabah local government finances - Awang Marikan, Dayang Affizah; Habibullah, Muzafar Shah; Wan Ngah, Wan Azman Saini (Faculty of Economics and Management, Universiti Putra Malaysia, 2006)
This paper is concerned with the issue of the intertemporal relationship between revenues and expenditures and the way in which a state government deals with the management of their public deficits. in this study, different hypotheses are considered to examine such problems. the so-called tax-spend hypotheses postulates that governments raise tax revenues ahead of engaging in new expenditures. the spend-tax hypothesis, on the other hand, predicts that governments spend first and then increases tax revenues to finance their expenditures. The spend-tax hypothesis, on the other hand, predicts that government spend first and then increases tax revenues to finance their expenditures. There is also the fiscal synchronization hypothesis that suggest that governments take decisions about revenues and expenditures simultaneously. Lastly, there is the possibility of independence as regards the decisions to spend and raise revenues. Using annual data on revenues and expenditures for 16 municipalities in Sabah over the period 1965 to 2003, empirical analysis from our vector error correction models suggest that the results are at the best mixed.